THE EFFECT OF CAFE ATMOSPHERE, PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER SATISFACTION AT PREMIUM COFFEE STATIONS IN LHOKSEUMAWE CITY FOR THE 2020-2021 PERIOD - Edyansyah, T; Ilham, Rico Nur; Ahyar, Juni; Chalirafi, Chalirafi; Sullaida, Sullaida (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
The purpose of this study was to examine the effect of cafe atmosphere, product quality and service quality on customer satisfaction at premium coffee stations in lhokseumawe. The population in this study were all customers at the premium coffee station in lhokseumawe. While the sample is 100 respondents. The sampling technique is accidental sampling. The type of data used in this study is primary data in the form of cross selection data obtained by using a questionnaire. The method of data analysis in this study is the multiple linear regression analysis of panel data. The results of the study found that partially the cafe atmosphere had a significant influence on consumer satisfaction, partially product quality had an effect on consumer satisfaction, while partially service quality has an effect on customer satisfaction. and cafe atmosphere product quality and service quality simultaneously affect customer satisfaction.